An improved process to produce high surface area nanoparticle vanadium phosphorus oxide catalysts and product derives thereof - Yap, Taufiq Yun Hin; Rownaghi, Ali Asghar (2007)
An improved process to produce high surface area nanoparticle vanadium phosphorus oxide catalysts comprises the steps of reducing vanadium-containing compounds in an alcohol solution selected from the group consisting of isobutanol and benzyl alcohol and any combination derives thereof under reflux for 4 to 6 hours to form a suspended mixture; reacting dopants and phosphorus-containing compounds to the suspended mixture under reflux for 30 minutes to 3 hours to form precursors of the vanadium phosphorus oxide catalysts; drying the formed precursors; and calcining the dried precursors in a flow of gaseous n-butane/ air mixture at 400 to 460c to form activated vanadium phosphorus oxide catalysts.